Pemanfaatan Radio dan Sosial Media Sebagai Media Promosi Kesehatan Pencegahan Obesitas pada Remaja - Sarni Anggoro (Humanism: Journal of Community Empowerment (HJCE), 2022)
Obesity in adolescents are serious condition that must be addressed immediately so as not to interfere with the quality of life. Obesity in adolescents can cause physical and psychological problems for adolescents. The purpose of community service with the theme of preventing obesity in adolescents is intended so that adolescents know the meaning, causes, consequences and management of obesity. The method used in this activity was health promotion with lectures and answering questions. The media used were mass media such as radio, facebook, twitter, instagram, and youtube from the business of the Radio Management company Qolbu 92.3 FM (MQFM) Jogja. The results of community service carried out are activities run smoothly, all materials had been delivered at the given time. There were listeners who follow the activity and ask questions and had been answered clearly. Meanwhile, on Facebook, Twitter, Instagram, and YouTube media, the schedule of activities and a summary of the material have been uploaded. The conclusion obtained from health promotion activities with the theme of preventing obesity in adolescents are running smoothly and have been implemented. This activity does not compare the results of the achievement of the recipient of the message but sees the implementation of the activity. The use of the right media is one of the right steps so that the information conveyed is right on target. Health promotion targeting adolescent can use social media that is often accessed by adolescent such as radio, facebook, twitter, instagram and youtube.Keywords: obesity, health promotion, radio, social media, adolescents